Impact of Defibrotide in the Prevention of Acute Graft-Versus-Host Disease Following Allogeneic Hematopoietic Cell Transplantation. Issue 9 (September 2022) - Tilmont, Rémi; Yakoub-Agha, Ibrahim; Ramdane, Nassima; Srour, Micha; Coiteux, Valérie; Magro, Léonardo; Odou, Pascal; Simon, Nicolas; Beauvais, David
Background: Defibrotide is indicated for patients who develop severe sinusoidal obstructive syndrome following allogeneic hematopoietic cell transplantation (allo-HCT). Preclinical data suggested that defibrotide carries a prophylactic effect against acute graft-versus-host disease (aGVHD). Objective: The purpose of this study was to investigate the effect of defibrotide on the incidence and severity of aGVHD. Methods: This single-center retrospective study included all consecutive transplanted patients between January 2014 and December 2018. A propensity score based on 10 predefined confounders was used to estimate the effect of defibrotide on aGVHD via inverse probability of treatment weighting (IPTW). Results: Of the 482 included patients, 64 received defibrotide (defibrotide group) and 418 did not (control group). Regarding main patient characteristics and transplantation modalities, the two groups were comparable, except for a predominance of men in the defibrotide group. The median age was 55 years (interquartile range [IQR]: 40-62). Patients received allo-HCT from HLA-matched related donor (28.6%), HLA-matched unrelated donor (50.8%), haplo-identical donor (13.4%), or mismatched unrelated donor (7.0%). Stem cell source was either bone marrow (49.6%) or peripheral blood (50.4%). After using IPTW, exposure to defibrotide was not significantly associated with occurrence of aGVHD (HR = 0.97; 95% CI 0.62-1.52; P = .9) or occurrence of severe aGVHD (HR = 1.89, 95% CI: 0.98-3.66; P = .058). Conclusion and Relevance: Defibrotide does not seem to have a protective effect on aGVHD in patients undergoing allo-HCT. Based on what has been reported to date and on these results, defibrotide should not be considered for the prevention of aGVHD outside clinical trials.